Agile Processes in Software Engineering and Extreme Programming: 21st International Conference on Agile Software Development, XP 2020, Copenhagen, Denmark, June 8-12, 2020, Proceedings - Stray, Viktoria; Hoda, Rashina; Paasivaara, Maria; Kruchten, Philippe (Lecture Notes in Business Information Processing, 2020)
This open access book constitutes the proceedings of the 21st International Conference on Agile Software Development, XP 2020, which was planned to be held during June 8-12, 2020, at the IT University of Copenhagen, Denmark.However, due to the COVID-19 pandemic the conference was postponed until an undetermined date.